INVESTIGATION OF DIFFERENT DARK MATTER PROFILES - K. Boshkayev; G. Zhumakhanova; K. Mutalipova; M. Muccino (Academic Scientific Journal of Computer Science, 2019)
Different, commonly accepted and widely used phenomenological dark matter profiles such as the pseudo-isothermal sphere, Burkert, Navarro-Frenk-White, Moore and Einasto profiles are employed to estimate the mass distribution of dark matter in various galaxies. The Newtonian gravity is involved to perform computations at large galactic scales. The distribution of dark matter in diverse types of galaxies is assumed to be spherical without taking into account the complex structure of galaxies such as their cores, inner and outer bulges, disks and halos. The theoretical rotation curves are overlapped with the observations for each individual galaxy. By means of the least square algorithm the model parameters are inferred from the observational data and are subjected to the Bayesian information criterion, which identifies the more preferred model. The masses of dark matter are calculated for each galaxy, with all listed profiles, and compared with the visible masses of the galaxies. The results are in agreement with the ones in the literature.